KAJIAN RASIO STRUKTUR BANGUNAN BERTINGKAT - Hariyawaningsih, Ervina; Gondokusumo, Onnyxiforus (Jurnal Muara Sains, Teknologi, Kedokteran dan Ilmu Kesehatan, 2020)
Cost estimation is an activity for estimating costs, resources and risks in order to start and complete a project. Generally, at initial stage, most estimation data is not complete. Therefore, to estimate the quantity of structure we often uses structure ratio. The structure ratio in this research is the ratio of concrete, the ratio of iron and the multiplication between the ratio of concrete with the ratio of iron. Analysis conducted to look for similarity in structure ratio between building functions and between consultans, the influence of the number of floors to the value of structure ratio, find the intervals and average structure ratios, find the effect of earthquake regulations on rising structure ratios and find regression equation for structure ratio. From the analysis results, it is found that the average structure ratios between buildings and between consultans are same. The number of floors affects the value of the iron ratio and multiplication between the ratio of concrete to the ratio of iron. Based on the analysis using the confidence interval estimate, the lower, upper and average limits of the concrete ratio, iron ratio, and multiplication between the ratio of concrete to iron ratio in ≤ 2012 and in> 2012. Changes in earthquake regulations affect the value of the structure ratio, the increase of concrete ratio reaches 8.8%, the iron ratio reaches 19,2% and the multiplication between the ratio of concrete and iron reaches 27,9%. In this research, there is no regression equation was obtained for the concrete ratio, the iron ratio and the multiplication between the ratio of concrete to iron ratio. ABSTRAKEstimasi biaya merupakan sebuah kegiatan untuk memperkirakan biaya, sumber daya dan risiko-risiko agar dapat memulai dan menyelesaikan suatu proyek. Pada tahap awal estimasi, umumnya data yang tersedia belum lengkap. Oleh karena itu, untuk menghitung biaya pekerjaan struktur seringkali menggunakan rasio struktur. Pada penelitian ini rasio struktur yang akan dianalisis adalah rasio beton, rasio besi dan perkalian antara rasio beton dengan rasio besi. Analisis ini dilakukan untuk mencari kesamaan rasio struktur antar fungsi bangunan dan antar konsultan, pengaruh jumlah lantai dengan nilai rasio struktur, mencari interval dan rata-rata rasio struktur, mencari pengaruh peraturan gempa terhadap kenaikan nilai rasio struktur dan mencari persamaan regresi rasio struktur. Dari hasil analisis didapatkan rata-rata rasio struktur antar bangunan dan antar konsultan memiliki nilai yang sama. Jumlah lantai berpengaruh terhadap nilai dari rasio besi dan perkalian antara rasio beton dengan rasio besi. Berdasarkan hasil analisis dengan mengunakan confidence interval estimate diperoleh batas bawah, batas atas dan rata-rata pada rasio beton, rasio besi, dan perkalian antara rasio beton dengan rasio besi pada tahun ≤ 2012 dan tahun > 2012. Adanya perubahan pada peraturan gempa mempengaruhi nilai rasio struktur, yaitu pada rasio beton kenaikan mencapai 8,8%, rasio besi mencapai 19,2% dan perkalian antara rasio beton dan rasio besi mencapai 27,9%. Pada penelitian ini tidak diperoleh persamaan regresi untuk rasio beton, rasio besi dan perkalian antara rasio beton dengan rasio besi.